KONSEP JIHAD ABU BAKAR BAASYIR DALAM PERSFEKTF FILSAFAT ABSURDISME ALBERT CAMUS - Neng Hannah; Yudistira Ananda Setiadi (JURNAL AL-AQIDAH, 2022)
Islam is a religion salvation. But now there are some assumption that Islam is a religion that teaches violence. The purpose of this study is to dissect one of the concepts of jihad that was coined by Abu Bakar Baasyir throught the philosophical approach of absurdism. This research was conducted using qualitative methods through literature study. The result of this study indicate that the concept of jihad Abu Bakar Baasyir is a formof absurdity and the call for jihad and jihad itself is another form of absurdity. This study recommends that the concept of jihad Abu Bakar Baasyir is also studied through other philosophical or theological approaches that are more in line with the discusson.